2015
DOI: 10.1080/22243534.2015.11828345
|View full text |Cite
|
Sign up to set email alerts
|

All at sea: Insights into crew work experiences on a cruise liner

Abstract: This research explores employee experiences of working on board a cruise ship. Cruise liners have been described as floating hotels; but increasingly they are more like floating resorts, embracing passenger and crew populations as big as small towns. In addition to the usual service sector experiences and emotional labour requirements of service jobs in the hospitality sector, the shipboard context in which employees live and work put considerably further constraints and pressure on crew. This paper reports on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…The fixed physical and unique social boundaries are both a home and workplace for individuals, fostering a cultural atmosphere that is shared with others (Weeden, Woolley, & Lester, 2010). Previous research looking at employment conditions in the cruise ship industry (see Bolt & Lashley, 2015;Clancy, 2017;Klein, 2002;Terry, 2011Terry, , 2014 have studied: level of pay, contract length, hours worked, recruitment practices, hierarchical systems, etc. The research suggests work on a ship is in part sacrificial, yet within the secure and restrictive sense of themselves and others within the interactions and conditions of an occupied physical and social environment/space.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fixed physical and unique social boundaries are both a home and workplace for individuals, fostering a cultural atmosphere that is shared with others (Weeden, Woolley, & Lester, 2010). Previous research looking at employment conditions in the cruise ship industry (see Bolt & Lashley, 2015;Clancy, 2017;Klein, 2002;Terry, 2011Terry, , 2014 have studied: level of pay, contract length, hours worked, recruitment practices, hierarchical systems, etc. The research suggests work on a ship is in part sacrificial, yet within the secure and restrictive sense of themselves and others within the interactions and conditions of an occupied physical and social environment/space.…”
Section: Introductionmentioning
confidence: 99%
“…There is limited research regarding the work and life of cruise workers (Bolt & Lashley, 2015;Dennett, Cameron, Bamford, & Jenkins, 2014;Gibson & Perkins, 2015;Lee-Ross, 2008). Knowledge in this area can provide employers, recruiting agencies, and potential seafarers with valuable insights into one of the fastest growing sectors in the tourism industry (Clancy, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If it is seen from the side of opportunity, working on cruise ships, especially for workers from developing countries, is a chance to improve their economic condition. Bolt and Lashley (2015), in their study, found that salaries are the primary reason that drives workers to work on cruise ships. Similarly, a study by Artini and Nilan (2014) stated that working on cruise ships is closely related to the idea of a prosperous future.…”
Section: Is It An Opportunity or Exploitation?mentioning
confidence: 98%
“…In addition to the passenger load, there is also approximately 250,000 staff 1 who work onboard cruise ships (Crew Centre, 2017). However, this is an estimate as the industry has highly variable regulation and amounts of staff transparency around the world, staff are often employed on a casual, fixed term basis, from a large variety of countries, and there is high staff turnover (Bolt & Lashley, 2015).…”
Section: Introductionmentioning
confidence: 99%